SYMBOLIC PLAY IN CHILDREN WITH AUTISM SPECTRUM DISORDER - Jabbarov, Rashid; Nazarova, Aydan (Health and Society, 2025)
Children with Autism Spectrum Disorder (ASD) exhibit persistent deficits in social communication and interaction, restricted and repetitive behaviors, and stereotyped behaviors. Studies have been conducted on the differential development of children with ASD in activities that require imagination and creativity. Studies comparing children with ASD with typically developing children or children with other developmental disabilities, particularly in terms of imaginative symbolic play, are important for understanding both the development of symbolic play in ASD and cognitive development. This review discusses the various ideas that encompass empirical studies investigating the development of symbolic play in children with ASD and the meaning of such play, and attempt to explain the limitations observed with ASD. The studies reviewed show that children with ASD differ from control groups in the development of spontaneous symbolic play (e.g., spending less time on this play, constructing less complex games), and the sources of the observed differences may be related to both ability and performance.